Software Size Estimation: A survey - AL-Saleem, Aeshaa L .; Hammo, Asma’a Y. (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Software size prediction is a first step to compute information for software project development such as: project cost, effort, schedules, duration and so on. This paper presents the software prediction methods and the efforts of the researchers in this era. Methods such as Source line of Code, Model based estimation, function point and estimation from UML diagrams. For every method, the strength and weakness is presented. Also, it presents the evaluation criteria that is necessary for the researcher to evaluate the accuracy of the methods.This information will help the researcher in the future to choose the most effect method that fit to his/her software project.